2005
DOI: 10.1242/jcs.02608
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between secretogranin III and carboxypeptidase E facilitates prohormone sorting within secretory granules

Abstract: Secretogranin III (SgIII) and carboxypeptidase E (CPE) bind specifically to cholesterol-rich secretory granule (SG) membranes. We previously showed that SgIII binds chromogranin A (CgA) and targets CgA to the SGs in endocrine cells. We investigated the binding of SgIII and CPE because they frequently localize close to the periphery of SGs, and they bind each other in mouse corticotrope-derived AtT-20 cells. In Cpefat mouse corticotropes, which have defective CPE, proopiomelanocortin (POMC)-derived adrenocortic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
77
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(84 citation statements)
references
References 43 publications
7
77
0
Order By: Relevance
“…Pancreatic beta cells and beta cell lines are also known to synthesise, in addition to insulin, a number of other secretory proteins, including members of the granin family, chromogranin A and chromogranin B (CgB) [7][8][9][10]. Based on intracellular distribution studies [7,8] and on data obtained in other cell lines (AtT20 and PC12), these granins are believed to play important roles both in the sorting, packaging and processing of secretion products [11][12][13][14], and in the storage of Ca 2+ within SG lumina [15]. Moreover chromogranin A and/or peptides derived from its processing have been reported to play autocrine, paracrine and endocrine functions upon discharge [16][17][18][19], while CgB has been shown to induce an autocrine inhibition of insulin release from beta cells [20].…”
Section: Introductionmentioning
confidence: 99%
“…Pancreatic beta cells and beta cell lines are also known to synthesise, in addition to insulin, a number of other secretory proteins, including members of the granin family, chromogranin A and chromogranin B (CgB) [7][8][9][10]. Based on intracellular distribution studies [7,8] and on data obtained in other cell lines (AtT20 and PC12), these granins are believed to play important roles both in the sorting, packaging and processing of secretion products [11][12][13][14], and in the storage of Ca 2+ within SG lumina [15]. Moreover chromogranin A and/or peptides derived from its processing have been reported to play autocrine, paracrine and endocrine functions upon discharge [16][17][18][19], while CgB has been shown to induce an autocrine inhibition of insulin release from beta cells [20].…”
Section: Introductionmentioning
confidence: 99%
“…It is clear that CgA and CgB act as cargo precursors that are proteolytically cleaved to form bioactive peptides. In addition to being sources of granule content in the form of proteolytically derived peptides, Chromogranins have also been described to chaperone secretory granule components (1,3,9,33,34). Chromogranins have also been described as cholesterol binding proteins, and a model for their role in the cholesterol sequestration events that participate in granulogenesis has been derived from several studies (35).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in mast cells, as in sympathoadrenal AtT-20 cells (16,35), a functional interaction between SgIII and CgA seems to be required for their granulogenic capacity. Hosaka and coauthors (34,35) have suggested that SgIII binds to the amino terminus of CgA thereby initiating the secretory granule biogenesis in the AtT-20 cells. This SgIIICgA complex binds to the cholesterol moieties within the secretory granule membrane, but the exact mechanism by which this binding promotes granulogenesis is not yet fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…42 GST fused to the p63 DBD was immobilized on beads, followed by incubation in the presence or absence of p28 (10-100 mole excess). Whole-cell lysates containing Cop1 and Pirh2 were prepared from MCF-7 cells in PBS containing 0.1% Triton X-100, 10% glycerol, and a protease inhibitor cocktail (Sigma-Aldrich).…”
Section: Cell Culturementioning
confidence: 99%